Exploring Synergistic Effects of Natural Antifungals and Metal Ferrocyanides for Enhanced Medicinal Applications - Tewari, Brij Bhushan; Roberts, Sharlene; Tiwari, Ashish Kumar (Chemistry and Biochemistry: Research Progress Vol. 1, 2025)
Natural products are one of the most consistently successful sources of drug leads. In recent decades, research activity into the clinical potential of this class of compounds in disease has increased. Metal complexes offer unique opportunities due to their ability to alter pharmacology, improving efficacy and reducing the negative side effects of drug molecules. The presented book chapter aimed to report the synergistic effects of antifungal activity of medicinal plants with metal hexacyanoferrate (II) complexes against various fungal infections. Manganese, Silver and Titanium ferrocyanides were synthesized and characterized by elemental and spectral studies. The stabilities of these metal ferrocyanides were investigated in the presence of acids, bases, organic solvents, and tap and seawater in the room and at boiling temperature. The natural antifungal plants studied were Azadirachta indica (Neem), Ocimum sanctum (tulsi), Cassia obtusifolia (money bush), Cassia alata (canicro bush), Tagetes patula (marigold). The natural antifungal plant extract with metal ferrocyanides complexes was found to have more antifungal properties in comparison to metal ferrocyanides and natural antifungals alone. Antifungal activity of natural antifungals, metal hexacyanoferrate (II) compound and natural antifungal metal ferrocyanide complexes were tested by a well-known cultured fungus (Aspergillus niger). The titanium ferrocyanide with neem extract and manganese ferrocyanide with money bush extract complexes were found to have maximum and minimum antifungal property, respectively. In conclusion, the antifungal activity of secondary metabolites is enhanced through interactions with metal ferrocyanides and metal ferrocyanides – natural products complexes may serve as an effective treatment for skin infections, warranting further investigation into its medicinal potential.